The Correlation of Blood Glucose with Salivary Glucose Level in Diabetic Patients - Arash Azizi; Ali Modaberi (Islamic Dental Association of Iran, 2014)
Background and Aim: Finding a relationship between the blood glucose level and its concentration in other body fluids such as the saliva can help in developing a conservative method for blood sugar assessment replacing venous sampling .The aim of this study was to evaluate the relationship of blood glucose level with salivary glucose in diabetic patients .   Materials and Methods: This case-control study was conducted on 75 diabetic patients as the case and 75 healthy subjects as the control group. Blood and salivary glucose levels were measured in the two groups. Pearson's correlation coefficient was used to assess the correlation of blood glucose with salivary glucose in the two groups .   Results: The mean ( ±SD) blood glucose and salivary glucose level was 247±24.2mg/dl and 1.4±0.2mg/dl in the case   group, respectively. These rates were 84.97±15.8 and 1.09±0.12mg/dl in the control group, respectively.   Statistical analyses showed a high correlation between blood glucose level and salivary glucose in diabetic patients (r =0/9) whereas this correlation was insignificant in the healthy control group (r = 0.18) .   Conclusion: This study showed a high correlation between blood glucose level and salivary glucose in diabetic patients .